'They say "I did it", but they don't say "I got an STI from it"': Exploring the experiences of youth with a migration background with sexual health in Amsterdam, the Netherlands. Issue 9 (2nd September 2022) - de Gee, Floor; Manuels, Carien; Boerwinkel, Elisabeth K.; Yap, Kenneth; Muntinga, Maaike E.
ABSTRACT: Youth with a migration background are underserved by sexual healthcare. Insight in their experiences is essential to develop tailored services and counter disparities. We explored how youth with a migration background access sexual health information, experience public sexual healthcare, and navigate sexual health in their particular sociocultural contexts. We carried out nine semi-structured interviews and one group interview with twelve young people (18–24) with a migration background in Amsterdam, the Netherlands. Respondents were heterosexually oriented and of various sociocultural backgrounds. Data were analysed using thematic content analysis. Three themes emerged: 'Access to sexual health information', 'Access to primary sexual health care', and 'Strategies for sexual self-care'. Youth sought out information online or from peers, however, conversations mostly focussed on pleasure while risk was often not discussed. Youth valued anonymity when accessing sexual healthcare, and used several strategies, such as staying silent or adhering to values such as 'self-respect', to navigate sexual health within their everyday gendered environments. While these strategies manifested as sources of empowerment, they also resulted in potential vulnerabilities. To counter sexual health disparities among youth with a migration background, public sexual health services should provide culturally safe care and foster participatory collaborations with local stakeholders.